Feline hypersomatotropism associated with insulin-refractory diabetes mellitus and favorable response to cabergoline therapy: a case report - Kamylla Moura Gadelha; Felipe Lucas de Carvalho Trajano; Romeika Kala dos Reis Lima; Marina Nogueira Monteiro; Lara Madruga de Almeida Rodrigues; Beatriz de Morais Silva; Emanoela Pereira de Mattos; Dhebora Crys dos Santos; Marina Clara Miranda Costa; Hebony Jhade Alves Silvério (Brazilian Journal of Animal and Environmental Research, 2026)
Hypersomatotropism (HST) is characterized by increased serum concentrations of growth hormone (GH) and insulin-like growth factor-1 (IGF-1), potentially resulting in acromegalic features, insulin resistance, diabetes mellitus (DM), nephropathy, organomegaly, cardiomyopathy, and other systemic abnormalities. This report describes the case of an elderly female cat with diabetes mellitus refractory to high-dose insulin therapy combined with an SGLT2 inhibitor. The patient presented primarily with nephropathy, adrenal and hepatic enlargement, pancreatitis, transient restrictive cardiomyopathy, enlarged paws, craniofacial bone enlargement, and prognathism. Based on the suspicion of HST, serum IGF-1 concentration was measured and contrast-enhanced computed tomography (CT) of the brain was performed, revealing an IGF-1 concentration >1,000 ng/mL and a pituitary mass within the sella turcica, respectively. These findings confirmed the diagnosis of hypersomatotropism secondary to a GH-secreting pituitary tumor. In addition to DM management, treatment was initiated with cabergoline at 10 μg/kg orally once daily (SID). The patient showed favorable clinical and laboratory responses, including improvement of acromegalic features and increased responsiveness to insulin therapy. (Scudder; Church, 2024).